Spatial Analysis of Landslide-Prone Areas in Damer District, Maluku Barat Daya Regency, Maluku Province - Henrich Rakuasa; Daniel Anthoni Sihasale; Philia Christi Latue; Yamres Pakniany; Juan Steiven Imanuel Septory (Social Science Studies, 2023)
Based on historical data on landslide events, Damer District is an area prone to landslides in Southwest Maluku Regency. One of the first steps in mitigating landslides in Damer District is to map areas that have the potential for landslides. The purpose of this study was to determine the spatial distribution of landslide-prone areas in Damer District, Southwest Maluku Regency. This study uses the SMORPH method to identify and classify areas that have the potential for landslides based on the matrix between the shape of the slope and the angle of the slope. This study resulted in 4 levels of landslide potential areas, namely very low, low, medium and high potential. Villages with high landslide potential are Wulur Village and villages with very low landslide potential are Ilih Village. The results of this study also illustrate that the higher the slope accompanied by the formation of convex or concave slopes, the higher the potential for landslides to occur. The results of the research are expected to help the Southwest Maluku Regency government, especially the Damer District government, in an effort to spatial planning based on disaster mitigation.Spatial Analysis